Exploring the Potential of Medicinal Plants on Fish Resilience to Aeromonas hydrophila Infection: A Comprehensive Study of Immunology, Biochemistry, Growth and Survival - Alokesh Kumar Ghosh; Shikder Saiful Islam; Abul Farah Md. Hasanuzzaman (Aquaculture, Fish and Fisheries, 2025)
ABSTRACT Aeromonas hydrophila, an omnipresent bacterium that infects a wide range of hosts, is responsible for massive mortality and significant financial losses among farm‐raised fish species. To control bacterial diseases in aquaculture systems, inappropriate antibiotic therapy is commonly practised, leading to the development of antibiotic‐resistant bacteria (ABR); using medicinal plants and/or extracts can be an alternative to antibiotics, thereby reducing dependency on antibiotics. Thus, a comprehensive prospecting into medicinal plant extracts to combat A. hydrophila infection in aquaculture is necessary. The immunostimulant characteristics of medicinal plants have generated a rising interest in their use in aquaculture. The present review examined the potential impact of plant extracts on the haematological, biochemical and immunological factors that might influence the general health of the fish as well as combat infection against A. hydrophila. The analysis revealed that the essential haematological parameters (haematocrit, haemoglobin, erythrocyte count and leukocyte count) and biochemical and immunological parameters (plasma glucose, cholesterol, triglycerides, albumin, total proteins, aspartate aminotransferase, alanine aminotransferase, phagocytic activity, respiratory burst activity and antioxidant activity) of fish were significantly improved when fish were fed with the extracts treated diet. Additionally, the growth parameters and survival rate of fish in the extract‐treated group were found to be significantly increased subsequent to exposure to A. hydrophila. The findings emphasize the capacity of plant extracts to serve as eco‐friendly substitutes for conventional therapies in aquaculture by enhancing fish health and resistance to diseases.